Tensile Load of Three-Menber Connection of Coconut and Bangkirai Lumber - Perpustakaan UGM, i-lib ([Yogyakarta] : Kantor Wakil Rektor Bidang Kemahasiswaan dan Alumni UGM, 2003)
Although Coconut wood is not known in Peraturan Konstruksi Kayu Indonesia 1961 (PICK1), research on the use Coconut wood as a construction material has been initiated by Morisco et al (1998) and Rofaida (1999). According to their research, the strength of Coconut wood decreases from bottom part to upper part of trunk. Therefore, people only use the bottom part of Coconut lumber for the. structural construction. This research observed the possibility of using the middle part of Coconut wood that was combined with Bangkirai wood in three-member connection and found out its connection yield load. The angle of connection (angle between Bangkirai lumber and Coconut lumber) was grouped into 0°, 45°, 60°, and 90°. Two bolts of 5/8" in diameter were used as connectors. The theoretical connection yield load was derived from Suwarno's (1986) and in the PKKI 2000 Draft. The result showed that the connection yield load decreased as the angle of connection increased. The experimental nominal strength of bolt of some connections of angle 45°, 60°, and 90° was lower than the that of theoretical strength of the PKKI 2000 Draft. The experimental nominal strength of bolt of all connection was higher than that of theoretical strength of Suwarno's (1968). The connection yield load of three-member connection of Coconut and Bangkirai lumber can he graded as the class 1 in PKKI 1961. Key words: Coconut wood, bolt, angle, strength